Association of Regular Thrombus Surface Phenotype With Complete Recanalization in First-Line Contact Aspiration Thrombectomy for Basilar Artery Occlusion - Kaiser, Daniel; Krukowski, Pawel; Hädrich, Kevin; Winzer, Robert; Pallesen, Lars-Peder; Gawlitza, Matthias; Linn, Jennifer; Puetz, Volker; Gerber, Johannes C. (Frontiers in Neurology, 2021)
Objective: To assess whether angiographic thrombus surface phenotype has an impact on efficacy of contact aspiration (CA) thrombectomy in patients with basilar artery occlusion (BAO). Methods: From January 2016 to December 2019, consecutive stroke patients with a BAO and first-line CA were analyzed in this retrospective study. We assessed baseline and imaging characteristics and treatment and clinical outcomes. We rated thrombus surface phenotype on pre-treatment digital subtraction angiography in a three-reader-consensus setting. Primary outcome was complete recanalization (modified treatment in cerebral ischemia [mTICI] 3 and arterial occlusive lesion [AOL] 3) after first-line CA without additionally stent retriever passes. Data analysis was stratified according to thrombus surface phenotype and complete first-line recanalization. Results: Seventy-eight patients met the inclusion criteria. Median age was 74 years (IQR 64–80), 64% were male, and median baseline NIHSS score was 24 (IQR 7–32). Thirty patients had a regular and 16 patients had an irregular thrombus phenotype. Thrombus surface was not assessable in 32 patients. In patients with a regular phenotype, complete recanalization was more often achieved compared to irregular and non-ratable phenotypes (50 vs. 18.8% and 21.9%; p = 0.027). Patients with a regular phenotype [odds ratio [OR] 8.3; 95% confidence interval [CI]: 1.9–35.8; p = 0.005], cardioembolic stroke (OR 12.1, 95% CI: 2.0–72.8; p = 0.007), and proximal end of the thrombus in the middle basilar artery segment (OR 5.2, 95% CI: 1.0–26.6; p = 0.046) were more likely to achieve complete recanalization after first-line CA without rescue therapy. Conclusion: The efficacy of CA may differ according to the angiographic thrombus surface phenotype in patients with BAO. A regular phenotype is associated with higher rates of complete recanalization in first-line CA. However, assessment of thrombus phenotype is frequently not feasible in BAO.